Asymmetrical Load Balancing using Reactive Components - Nguyen, Quoc Minh; Vo, Ta Dong; Nguyen, Duy Minh (Old Journal, 2018)
In practical three-phase power systems, unbalance operating condition is normally caused by several factors. Some factors are directly related to the asymmetrical structure of the power grid, such as overhead transmission lines, transformers, which leads to different voltage drops at each phase. However, the most accountable factors contributed to the unbalance condition of the network is the load diversity. In typical power distribution systems, loads can be connected in three-phase, single phase between two lines or single phase between line and neutral. Unbalance loads can range from several kW to MW levels such as furnace or electric rail track. Under heavy unbalance load condition, the significant amount of negative voltage and current sequences can cause negative impact on the power systems by introducing more heat losses in windings, damaging rotating machine and reducing efficiency. Recent studies show that unbalance operating condition caused by asymmetrical load can be compensated by using reactive elements [1-4]. In this paper, the effect of using reactive components will be examined in detail. The simulation will be performed in PSCAD for validation of the method.